2018
DOI: 10.12669/pjms.345.15102
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of incidental fatty liver on ultrasound and its association with diabetes mellitus and hypertension

Abstract: Objective:To see the frequency of incidental fatty liver on ultrasound and its association with diabetes mellitus and hypertension.Methods:A cross sectional study was conducted from January 2016 to June 2016 in the department of Surgery and Radiology at Hamdard University Hospital. Patients of both genders and all ages were selected by non purposive convenience sampling. Critically ill, trauma cases and all those patients who had a history of chronic liver disease, alcohol intake and expected pregnancy were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…We also found in our study that there was a highly significant statistical difference between study groups as regard random blood sugar (RBS) (p<0.001). This result agrees with the study of Zubair et al (13) who reported that diabetic patients are at strong risk for both NAFLD and NASH and there is a significant association of fatty liver with DM. Another study explained that the close association between NAFLD and type 2 DM lies in that they have a common pathogenesis, which is insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…We also found in our study that there was a highly significant statistical difference between study groups as regard random blood sugar (RBS) (p<0.001). This result agrees with the study of Zubair et al (13) who reported that diabetic patients are at strong risk for both NAFLD and NASH and there is a significant association of fatty liver with DM. Another study explained that the close association between NAFLD and type 2 DM lies in that they have a common pathogenesis, which is insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Less often it can be associated with noticeable fatigue or discomfort in the right upper quadrant of the abdomen. It can be diagnosed unexpectedly, during an ultrasound examination (USG) performed for another reason or based on elevated serum of alanine transaminase (ALT) and aspartate aminotransferase (AST) liver enzymes [8,12].…”
Section: Hdl -High-density Lipoproteinmentioning
confidence: 99%
“…Other risk factors include hypertension (HTN) (Li et al , 2017) and cardiovascular disease (CVD) (Ma et al , 2017). The development of NAFLD is caused by multiple factors such as dietary habits and sedentary lifestyle (Zubair et al , 2018). NAFLD includes different degrees of hepatic disorders from a simple steatosis, up to cirrhosis and hepatocellular carcinoma (Zubair et al , 2018; Mullish et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The development of NAFLD is caused by multiple factors such as dietary habits and sedentary lifestyle (Zubair et al , 2018). NAFLD includes different degrees of hepatic disorders from a simple steatosis, up to cirrhosis and hepatocellular carcinoma (Zubair et al , 2018; Mullish et al , 2018). In addition to hepatic complications, NAFLD has some extra hepatic complications such as metabolic syndrome, T2DM, HTN (Zubair et al , 2018) and other metabolic disorders such as dyslipidemia and CVD (Huh et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation